2019
DOI: 10.1016/j.bbapap.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ricin A-chain (RTA) catalytic activity by a viral genome-linked protein (VPg)

Abstract: Ricin is a plant derived protein toxin produced by the castor bean plant (Ricinus communis). The Centers for Disease Control (CDC) classifies ricin as a Category B biological agent. Currently, there is neither an effective vaccine that can be used to protect against ricin exposure nor a therapeutic to reverse the effects once exposed. Here we quantitatively characterize interactions between catalytic ricin A-chain (RTA) and a viral genome-linked protein (VPg) from turnip mosaic virus (TuMV). VPg and its N-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Although the authors could find neither kcat nor Km values for the catalytic activity of ricin on hsDNA as a substrate in the literature, some parameters were attained with synthetic substrates or ribosomes under steady-state catalysis conditions [ 11 , 17 , 18 , 32 ]. In this sense, the kcat/Km value found in this work was reported in the same order of magnitude by Chen et al [ 18 ] (4.5 × 10 5 M −1 s −1 ) for ricin A-chain subunit activity with 14-base stem-loop RNA substrate, and close to that reported by Aitbakieva et al (3.8 × 10 6 M −1 s −1 ) [ 32 ] when using 28S rRNA substrate. In contrast, Tan et al [ 11 ] when using synthetic oligoribonucleotides and as by Sturm and Schramm [ 17 ] when using rabbit reticulocyte ribosomes or yeast ribosomes as substrate, reported higher kcat/Km values of 1.1 × 10 7 M −1 s −1 and 2.6 × 10 8 M −1 s −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the authors could find neither kcat nor Km values for the catalytic activity of ricin on hsDNA as a substrate in the literature, some parameters were attained with synthetic substrates or ribosomes under steady-state catalysis conditions [ 11 , 17 , 18 , 32 ]. In this sense, the kcat/Km value found in this work was reported in the same order of magnitude by Chen et al [ 18 ] (4.5 × 10 5 M −1 s −1 ) for ricin A-chain subunit activity with 14-base stem-loop RNA substrate, and close to that reported by Aitbakieva et al (3.8 × 10 6 M −1 s −1 ) [ 32 ] when using 28S rRNA substrate. In contrast, Tan et al [ 11 ] when using synthetic oligoribonucleotides and as by Sturm and Schramm [ 17 ] when using rabbit reticulocyte ribosomes or yeast ribosomes as substrate, reported higher kcat/Km values of 1.1 × 10 7 M −1 s −1 and 2.6 × 10 8 M −1 s −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The depurination reaction concomitant to the catalytic action of ricin was monitored for hsDNA concentrations ranging from 2.5 to 50 µM (Figure 2a), and with the overall reaction dependent on the substrate concentration. The dependence of the initial velocities obtained from fitting data to Equation (1) (vss) on hsDNA concentration follows a regular hyperbolic saturation form (Figure 2b Although the authors could find neither kcat nor Km values for the catalytic activity of ricin on hsDNA as a substrate in the literature, some parameters were attained with synthetic substrates or ribosomes under steady-state catalysis conditions [11,17,18,32]. In this sense, the kcat/Km value found in this work was reported in the same order of magnitude by Chen et al [18] [32] when using 28S rRNA substrate.…”
Section: Enzymatic Catalysis Of Ricinmentioning
confidence: 99%
See 1 more Smart Citation
“…Aitbakieva et al [ 107 ] demonstrated that VPg1–110, the N-terminal truncated variant of viral genome-linked protein (VPg) from turnip mosaic virus (TuMV), bound to RTA and abolished ricin’s catalytic depurination of 28S rRNA in vitro and in a cell-free rabbit reticulocyte translational system. In the cell-free rabbit reticulocyte translational system, the treatment of RTA with the synthetic VPg1–110 peptide resulted in complete inhibition of RTA activity on ribosomes.…”
Section: Chemical Inhibitorsmentioning
confidence: 99%